Synchronous Orbital and Gastrointestinal Metastases from Breast Cancer: A Case Report and Review of Literature - Ramawad Soobrah; Fiona Tsang; Veronica Grassi; Hassan Hirji; Sreelakshmi Mallappa; Robert Reichert (Case Reports in Oncological Medicine)
Breast cancer is the most common malignancy among women and is a significant cause of morbidity and mortality worldwide. With the advent of improved imaging techniques and screening programmes, only a small proportion of women present with metastatic disease. Metastases involving the gastrointestinal (GI) tract and orbit are rare occurrences. We describe the case of a woman with simultaneous GI and orbital metastases from breast cancer who initially presented with abdominal pain and blurred vision and also summarise a review of the literature.